HUBUNGAN POLA ASUH ORANG TUA DENGAN KEDISIPLINAN SISWA KELAS TINGGI SD ISTIQOMAH SICINCIN PADANG PARIAMAN - Septia Putri, Rahmi; Febrianti Sari, Winda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This research is motivated by the relationship between parenting styles and student discipline among upper-grade students at SD Istiqomah Sicincin, Padang Pariaman Regency. The underlying issues include students arriving late, not bringing homework, and not wearing the appropriate school uniform according to the designated days. Therefore, this study aims to determine the relationship between parenting styles and the discipline of upper-grade students at SD Istiqomah Sicincin, 2X11 Enam Lingkung District, Padang Pariaman Regency. This research is correlational in nature. The population in this study consisted of 50 students. The sample used was total sampling, involving all 50 students. The instrument and data collection technique used was a questionnaire, with the measurement scale being the Guttman scale. The data analysis techniques included descriptive data analysis, prerequisite tests (normality and homogeneity tests), determination coefficient analysis, and hypothesis testing. From the hypothesis test, the correlation analysis result showed rxy = 0.297. The strength of the relationship based on the determination coefficient test was found to be 8.82%. The significance test result showed that the calculated t-value was greater than the t-table value, with t_calculated = 2.155 > t_table = 1.67 at a 5% significance level (0.05), thus Ha is accepted and Ho is rejected. This means there is a significant relationship between parenting styles and student discipline. It can be concluded from this study that there is a significant relationship between parenting styles and the discipline of upper-grade students at SD Istiqomah Sicincin, Padang Pariaman.Keywords: Parenting_style, Student_Discipline